Biologics for the Management of Erythrodermic Psoriasis: An Updated Review - Potestio L; Camela E; Cacciapuoti S; Fornaro L; Ruggiero A; Martora F; Battista T; Megna M (Dove Medical Press, 2023)
Luca Potestio,1 Elisa Camela,2 Sara Cacciapuoti,1 Luigi Fornaro,1 Angelo Ruggiero,1 Fabrizio Martora,1 Teresa Battista,1 Matteo Megna1 1Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy; 2Dermatology Unit, Istituto Dermopatico dell'Immacolata - IRCCS, Rome, ItalyCorrespondence: Luca Potestio, Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email potestioluca@gmail.comAbstract: Erythrodermic psoriasis (EP) is a severe and rare variant of psoriasis (less than 3% of cases), characterized by generalized scaling and erythema affecting more than 90% of body surface area. Several systemic symptoms can be present in patients with EP such as lymphadenopathy, arthralgia, fever, fatigue, dehydration, serum electrolyte disturbances, and tachycardia making this condition a possible life-threatening disease, particularly if appropriate treatments are not performed. In this scenario, effective and safe therapies are required. Unfortunately, the rarity of EP makes head-to-head Phase III trials challenging, leading to the lack of established guidelines for its management. Globally, conventional systemic drugs such as cyclosporine, methotrexate, and retinoids often have contraindications linked to patients' comorbidities and have not shown a high profile of efficacy and safety. Recently, the development of biologic drugs including anti-tumor necrosis factor-α and anti-interleukin 12- 23, 23, and 17 has revealed favorable results for the management of plaque psoriasis, making them also a possible therapeutic option for EP disease. However, their use in EP is still off-label. The aim of our study was to review current literature on the use of biologic drugs for the treatment of EPs in order to offer a wide perspective on their possible application in EP management.Keywords: erythrodermic psoriasis, treatment, biologic drugs